Pemberdayaan Ekonomi Masyarakat Melalui Desa Wisata di Air Kulim - Mukhlis Mukhlis; Muhammad Romi; Yous Gunawan (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
COMMUNITY ECONOMIC EMPOWERMENT THROUGH TOURISM VILLAGES IN AIR KULIM. This community service program aims to enhance the economic and social capacity of the residents of Air Kulim Village, Mandau District, Bengkalis Regency, through the development of a community-based tourism (CBT) village. This approach positions the local community as the main actors in planning, implementing, and managing tourism activities to ensure sustainable and inclusive development. The implementation method consists of four main stages: preparation, training, mentoring, and evaluation. The training sessions covered the concepts of tourism village development, entrepreneurship, local product innovation, destination management, and digital marketing. The program involved 15 participants. Evaluation results showed an average increase of 41% in participants’ knowledge, the establishment of the Air Kulim Tourism Village Forum (FDWAK) as a community-based tourism organization, and the creation of five local flagship products along with three thematic tourism packages that have become new economic attractions. Community income increased by 20–25% after the program, supported by effective digital promotion. Beyond economic impact, the program fostered collective awareness of the importance of environmental conservation and community collaboration in developing sustainable tourism. Therefore, this program demonstrates that CBT-based empowerment can serve as an effective model for rural economic development and for strengthening local cultural identity in Bengkalis Regence.